P-13 Experiences of a nurse practitioner in the political, cultural and practice translation of a training program for advanced care planning (ACP) 'respecting choices' from the united states to the netherlands. (1st September 2015) - Billekens, P; Korfage, IJ; Rietjens, Judith AC; Notter, J
Abstract : Background: Globalisation occurs in health care as well as other domains of society. The ACP program 'Respecting Choices' appeared appropriate in the light of increasing patient autonomy, so was brought from the United States to The Netherlands in a research project by Erasmus Medical Centre in Rotterdam. Aim: To identify and resolve the challenges and dilemmas arising from the process of transforming health care programs from one country to a format appropriate for another country. Methods: Using symbolic interaction supported by elements of focused ethnography the journey involved in the cultural, political and practice translation of the training program was developed, described and reflected upon. The cyclic process of observe, ask, reflect was used to learn from the experiences and critical decision making processes arising along the journey. Results: The Respecting Choices program addresses subjects that are politically, culturally and personally sensitive. What initially appeared to be a practical program for implementation in The Netherlands proved to be complex and demanding for all involved. Differences in the culture and health care system became evident, but common goals in patient's autonomy were clear and connected the countries. Discussion and conclusion: Transferring health care programs and interventions to a country other than where it was developed poses specific challenges and dilemmas. The personal situation, beliefs and values of all involved have to be acknowledged and explored. Also detailed knowledge of both health care systems and medical/nursing education and training is essential. Translating a program across continents is more than just translating words.